Right-wing nationalism, populism, and religion: what are the connections and why? - Haynes, Jeffrey (Religion, state & society, 2021)
This collection focuses on right-wing nationalism, populism, and religion, both theoretically and empirically, with an emphasis on the following countries: Australia, India, Italy, Turkey, and the USA. Although not the same thing, nationalism and populism are said to be closely linked. Nationalists, like populists, may claim that there is but one ‘true religion’ – that is, their own and their followers’ – which helps focus their nationalist vision. They bring religion and culture into their arguments to encourage political changes in their favour. Nationalists may identify and target those they see as ‘enemies of the people’, said to be a serious threat to fulfilment of a nationalist future free from culturally ‘alien’ influences. While linking nationalism with religion is not new, what is more novel is the connecting of religion, nationalism, and populism. The contributions to this collection explore these issues theoretically, conceptually, and empirically.